Associated Sectors of Magnetic Recording System via Spatially Coupled LDPC Codes - Sirawit Khittiwitchayakul; Pornchai Supnithi; Watid Phakphisut (My University, 2021)
Spatially coupled low-density parity-check (SC- LDPC) codes have emerged as promising advanced error- correcting codes (ECC) for future high-density magnetic recording (MR) systems, which require excellent error-correcting performance and acceptable practical complexity. In the traditional MR systems, the non-associated sectors are generally used, whereby two consecutive sectors are independently decoded by ECC. In this work, we propose the associated sectors of MR systems in which the information stored in the previous sectors can be requested by ECC to reinforce the decoding of the current sector. Moreover, the proposed associated sectors can mitigate the rate-loss problem of SC-LDPC codes in the MR systems. We demonstrate the bit-error-rates (BERs) of SC-LDPC codes in the bit-patterned media magnetic recording (BPMR) systems with non-associated sectors and associated sectors. The simulation results show that the associated sectors help achieve significant performance gains compared to the non-associated sectors.
Keywords: Error Correcting Code Techniques; DNA and Biological Computing; Advanced Wireless Communication Techniques